[Rezension von: Das Architekturmodell : Werkzeug, Fetisch, kleine Utopie / hrsg. von Oliver Elser ; Peter Cachola Schmal. Unter Mitarb. von Teresa Fankhänel .... - Frankfurt a. M. : Deutsches Architekturmuseum [u.a.]; Zürich : Scheidegger & Spiess , 2012] - Miller, Wallis 1961- (2013)
In the summer of 2012 the German Architecture Museum (DAM) in Frankfurt was filled from top to bottom with models. Three hundred of them, give or take a few, clamored for visitors’ attention, asking them to shift their thinking about architecture from buildings to the artifacts of the design process. The models came from museums near – one-third were from the German Architecture Museum’s own collection – and far, including the Museum of Modern Art in New York; they came from private collections and architect’s offices in Germany and abroad. Models of Mies van der Rohe’s Seagram Building, Louis Kahn’s Meeting House at the Salk Institute, OMA’s design for the Parc de la Villette, Mendelsohn’s Einstein Tower, and O.M. Ungers’s building for the German Architecture Museum itself were interspersed among less familiar examples. These included Sergius Ruegenberg’s series of collaged models of houses, Gottfried Böhm’s plasticine models, Wolfgang Döring’s Space-Music Theater, Walter Jonas’s Intrapolis, and Conrad Roland’s elegant model of a Spiral Skyscraper from the 1960s, which welcomed visitors to the exhibition after having spent twenty-four years in a storage facility.
Keywords: architectural model, modernism, exhibition, Deutsches Architekturmuseum; Rezension